Risks in the Construction Project Procurement Process and the Mitigation Methods - Khumpaisal, Sukulpat (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Risk management in construction projects is considered as an important part of the management process. Since risk in construction projects associated with three major principles, which are Time, Cost and Quality. Those risks and uncertainties are caused by performance of workers, material and parts quality, delays in supply of important materials to site, project budget and cost control, or the complexity of project procurement processes, which may threaten the project objectives. This article will emphatically focus on risk, that is caused by the complexity of the construction procurement process. In addition, the appropriate risk identification methods will be also introduced in this article. Suggested methods shall start with setting up a risk profile, avoidance of risks, basic risk assessment and useful risk mitigation actions for project management participants, particularly architects or project managers to understand risks associated in construction procurement process including how to mitigate those risks.